Regulating vesicle bilayer permeability and selectivity via stimuli-triggered polymersome-to-PICsome transition - Wang, Xiaorui; Yao, Chenzhi; Zhang, Guoying; Liu, Shiyong (Nature communications, 2020)
Compared to liposomes, polymersomes of block copolymers (BCPs) possess enhanced stability, along with compromised bilayer permeability. Though polyion complex vesicles (PICsomes) from oppositely charged block polyelectrolytes possess semipermeable bilayers, they are unstable towards physiologically relevant ionic strength and temperature; moreover, permselectivity tuning of PICsomes has remained a challenge. Starting from a single component diblock or triblock precursor, we solve this dilemma by stimuli-triggered chemical reactions within pre-organized BCP vesicles, actuating in situ polymersome-to-PICsome transition and achieving molecular size-selective cargo release at tunable rates. UV light and reductive milieu were utilized to trigger carboxyl decaging and generate ion pairs within hydrophobic polymersome bilayers containing tertiary amines. Contrary to conventional PICsomes, in situ generated ones are highly stable towards extreme pH range (pH 2-12), ionic strength (~3 M NaCl), and elevated temperature (70 °C) due to multivalent ion-pair interactions at high local concentration and cooperative hydrogen bonding interactions of pre-organized carbamate linkages. Polyion complex vesicles have advantageous applications but have poorly tuneable permeability and nanostructure stability. Here, the authors develop polyion complex vesicles created using a stimuli-triggered transition from polymersomes and show high stability and switchable bilayer permaselectivity.